NURSING TEACHING DEGREE: THE TRAINING OF NURSING TEACHERS FOR SECONDARY-LEVEL PROFESSIONAL TECHNICAL EDUCATION - Corrêa, Adriana Katia; Clapis, Maria José; Rodrigues, Rosa Maria; Conterno, Solange de Fatima Reis (Cogitare Enfermagem, 2022)
Editorial